#1**+1 **

multiply the equation by 5 to get

5x - 5y - 5z = -15 now since 5y = 3x

5x - 3x - 5z = -15 multiply THIS equation by 1.6

8x -4.8x - 8z = -24 now since 8z = 3x

8x - 4.8x -3x = -24

x = -120

ElectricPavlov Jun 26, 2020

#2**0 **

It is good if we can express everything in terms of x. Because it will become a linear equation in one variable.

In fact, we can. Manipulating the first equation:

3x = 5y

y = 3x/5 = 0.6 x

3x = 8z

z = 3x/8 = 0.375 x

Then, we plug these into the equation:

\(x-0.6x-0.375x=-3\)

We simplify the left hand side:

\(0.025x = -3\)

Changing that 0.025 into a fraction gives

\(\dfrac x{40} =-3\\ \)

We multiply 40 to both sides to get

**x = -120**.

MaxWong Jun 26, 2020